IMPLEMENTASI TANGGUNG JAWAB PELAKU USAHA DALAM PRAKTEK PEMBULATAN PEMBAYARAN SEWA WARUNG INTERNET TERHADAP KONSUMEN DI KOTA PEKANBARU - Dinda Febriani Ramali; Firdaus '; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Consumer protection is a term used to describe the legal protectionafforded to consumers in an attempt to satisfy their needs from things that canharm consumers themselves. Consumer protection laws exist to protect consumersthemselves. Consumers must be critical in using that is by prioritizing "needs"rather than "wishes". Consumers must also be wary of the rounding of internetcafe rental payments made by business actors. The purpose of this thesis research,among others; First, to know the rights of consumers related to the rest of theinternet rental pay against the practice of rounding off internet cafes rentalpayments, Secondly, to find out why business practitioners do the practice ofrounding up payments for internet cafes, Third to know the efforts made bybusiness actors for consumer rights fulfilled in the internet rental.The type of research used by the authors is empirical law research or alsoknown as sociological law research, namely research conducted by way ofidentifying the law and how the effectiveness of law applies in society. Thisresearch was conducted in District Sail Pekanbaru while population and sampleare internet café user in Sail District. In this study data sources used, primarydata, secondary data, and tertiary data, data collection techniques in this studywith questionnaires, interviews, and literature study.From the research results of the problem there are three main things that can beconcluded First, the consumer's knowledge of his rights related to the rest of theinternet rental pay, Second, the business practitioners to practice the rounding ofinternet rental payments to consumers, Third what efforts made by business actorsfor rights consumers are fulfilled in internet rentals. Author suggestions.First, tothe community more active and smart and critical as consumers. Secondly,business actors should pay more attention to the rights of consumers themselves,Third, consumers should be more concerned with the losses incurred.Keywords: Liability - Consumer – Implementation